Evaluation of Diuretic and Antioxidant Properties in Aqueous Bark and Fruit Extracts of Pine - Shariati, Hadi; Hassanpour, Mohammad; Sharifzadeh, Gholamreza; Zarban, Asghar; Samarghandian, Saeed; Saeedi, Farhad (Current Drug Discovery Technologies, 2021)
Objective: The present study has been carried out to evaluate the diuretic and antioxidant properties of pine herb in an animal model. Materials and Methods: 45 adult male rats were randomly divided into nine groups including: groups I (the negative control), groups II (positive control, furosemide 10 mg/kg), groups III to VIII (treatment groups received 100, 200, 400 mg/kg of the aqueous extracts of bark and fruit) and group IX received the combination of aqueous extract of bark (100 mg/kg) and the fruit (100 mg/kg). The urine output, glomerular filtration rate (GFR), electrolytes, urea, and creatinine levels were evaluated. Furthermore, the phenolic content and antioxidant activity of both extracts were also assessed using 2, 2-diphenyl-1-picrylhydrazyl (DPPH), ferric reducing antioxidant power (FRAP) and Folin-Ciocalteu methods. Results: The aqueous extracts of the pine bark and fruit increased the urinary output in a dosedependent manner. The combination of the two extracts compared to the other extracts alone significantly increased the serum potassium level. This study also showed each extract increase creatinine clearance in a dose-dependent manner (p<0.01 and p<0.05). The increase of GFR in the combination group was not significant. The current data showed a significant increase in the total phenolic content in pine bark extract in compared with the fruit extract. Conclusion: The pine bark and fruit can be useful in the prevention and treatment of kidney stones due to the high diuretic properties and antioxidant activity.
Keywords: pine